2017
DOI: 10.5152/eej.2017.17004
|View full text |Cite
|
Sign up to set email alerts
|

3D Micro-CT Analysis of Void and Gap Formation in Curved Root Canals

Abstract: Objective: This study used microcomputed tomography (micro-CT) to compare the volumes of voids and gaps in curved root canals instrumented and filled using various techniques. Methods: Twenty extracted mandibular first molars with two curved mesial root canals were used. Root canals were instrumented using a self-adjusting file (SAF) or Revo-S file system. For standardization, mesiobuccal canals were instrumented with SAF and mesiolingual canals were instrumented with Revo-S in each root. The canals were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…The quantitative measurement of voids differed among the techniques. The results of one of the studies differed from the rest-it found fewer voids in the cold lateral condensation group [75]. These differences were not significant.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…The quantitative measurement of voids differed among the techniques. The results of one of the studies differed from the rest-it found fewer voids in the cold lateral condensation group [75]. These differences were not significant.…”
Section: Discussionmentioning
confidence: 70%
“…The presence of voids at the interface may promote bacterial proliferation from untouched root areas and lead to failure of treatment. Another study compared the self-adjusting file system to rotary techniques [75] and found fewer voids with rotary instruments in both obturation techniques (though statistically insignificant). It is known that the technique of instrumentation affects the completeness of obturation [36].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations